Impact Of An Asthma Care Programme On Process And Cost Outcome Amongst Children With Asthma In Two Major Hospitals In Malaysia - Zainal, Ramli (2012)
INTRODUCTION: Childhood asthma is one of the most common chronic diseases. Due to its high prevalence, asthma places a considerable economic burden on the health care system and society. Optimal management can help to control the disorder and various interventions have been put into place based on recommendations of clinical practice guidelines (CPGs). However despite the availability of these CPGs and effective pharmacotherapy, care often fall short of the accepted best practices. This study was aimed at assessing the current management of paediatric patients in terms of guideline adherence and to evaluate the impact of a structured Asthma Care Programme (ACP) on resource utilisation and cost associated with the management of asthma.